Entropy analysis of MHD hybrid nanofluid in a rotating channel filled with porous material - Emaline Joseph Ndelwa; Michael Hamza Mkwizu; Alex Xavery Matofali; Ahmada Omar Ali (International Journal of Thermofluids)
This study investigates entropy generation of MHD hybrid nanofluid in a rotating channel filled with porous material. The hybrid nanofluid, which uses Cu and alumina nanoparticles along with water as the base fluid, has been used. The hybrid model equations were solved numerically using MATLAB’s ode15s which employs Runge-Kutta–Fehlberg scheme. Effects of entropy generation and other system variables were investigated. Parametric analysis reveals that, hybrid nanofluids show better heat transport capacities with a higher Nusselt number than Cu–water and alumina-water nanofluids. Thus, because of its improved thermal characteristics, the hybrid nanofluid transfers more heat, which makes it a better option for applications that need effective heat dissipation. The results show that, increasing the Biot number reduces temperature, while hybrid nanofluids yield a higher Bejan number, indicating more efficient heat transfer with minimized entropy generation. The study identifies increased friction between fluid and porous media as the cause of temperature rise with higher porous media resistance and shape factor parameters. It is also depicted that, the rate of entropy generation decreases as the Biot number Bi rises, this happens as a result of the channel’s temperature gradient being less pronounced at higher Bi, which reduces thermal irreversibility and, in turn, entropy generation. The findings also demonstrate that the presence of a magnetic field reduces axial velocity while increasing transverse velocity. Consequently, skin friction increases in the axial direction and decreases in the transverse direction. In addition, the increase of rotational parameter has been found to reduce skin friction to the greatest extent. These findings underscore the potential of hybrid nanofluids in optimizing thermal systems by reducing entropy generation and enhancing heat transfer efficiency.